Discovery of novel pyrazolo[1, 5-a]pyridine-based EP1 receptor antagonists by scaffold hopping: Design, synthesis, and structure-activity relationships. Issue 17 (1st September 2017) - Nishigaya, Yosuke; Umei, Kentaro; Saito, Yoshifumi; Watanabe, Hiroyuki; Kondo, Tatsuhiro; Kondo, Atsushi; Kawamura, Naohiro; Tatani, Kazuya; Kohno, Yasushi; Tanaka, Nobuyuki; Seto, Shigeki
Graphical abstract: Abstract: A scaffold-hopping strategy towards a new pyrazolo[1, 5- a ]pyridine based core using molecular hybridization of two structurally distinct EP1 antagonists, followed by structure-activity relationship-guided optimization, resulted in the identification of potent EP1 antagonists exemplified by4c, 4f, and4j, which were shown to reduce pathological intravesical pressure in rats when administered at 1 mg/kg iv.